Social Science Diliman (2011)
Social Science Diliman: A Philippine Journal of Society and Change (SSD) is the flagship journal for the social sciences of the University of the Philippines Diliman. It is internationally refereed, semi-annual, and bi-lingual (in English and Filipino
). SSD publishes works on the social sciences and its applications, including multidisciplinary and interdisciplinary works that have a broad focus and will be of interest to scholars beyond a single discipline, area of study, and time frame. Book Rev
iews are also published.SSD provides immediate open access to its content on the principle that making research freely available to the public supports a greater global exchange of knowledge. Contents of this journal may not be reproduced except f
or noncommercial, personal, educational, and research purposes. In the same manner, publication in SSD does not entail article processing charges (APCs), submission charges, pages charges, color charges, and any similar charges.